The Role of AI-Powered Analytics in Building a Human-Centered Smart Campus - Delgado, Samantha Joyce; Panganiban, Nathaniel Joseph; Robles, Kimberly Anne (Etunas, 2023)
The rapid digital transformation of higher education has accelerated the adoption of smart campus technologies integrating artificial intelligence (AI), Internet of Things (IoT), and cloud computing. While existing initiatives often emphasize operational efficiency and infrastructure optimization, limited attention has been given to building human-centered smart campuses that prioritize student engagement, well-being, and academic success. This study investigates the role of AI-powered analytics in shaping adaptive, inclusive, and student-focused campus ecosystems, with an observational study conducted at De La Salle University (DLSU), Manila, Philippines. AI-driven analytics were deployed to process multi-source datasets, including IoT-enabled classroom sensors, learning management system (LMS) activity logs, and student survey feedback. The system generated predictive insights to identify at-risk learners, support personalized learning pathways, and recommend interventions for improved academic outcomes. Preliminary findings from the DLSU pilot revealed a 19% increase in course participation and a 12% reduction in dropout risk among vulnerable student groups. Additionally, real-time analytics enhanced campus services by optimizing space utilization, energy efficiency, and scheduling flexibility, indirectly improving student comfort and productivity. The results suggest that AI-powered analytics extend the smart campus paradigm beyond efficiency, enabling higher education institutions to foster human-centered learning environments that integrate inclusivity, well-being, and sustainability. By demonstrating how data-driven systems can support both academic and non-academic aspects of student life, this research positions AI as not only a technological enabler but also a catalyst for equitable and student-centered digital transformation in higher education.